Partnership Sought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
St. Jude Medical Centre: 'We are looking for partners who may be interested in establishing and running commercial ostrich farms and a laboratory for cattle-embryo transfer technology with us. We are practicing professional veterinarians,...